THE EFFECT OF BANK SOUNDNESS RATIO, SYSTEMATIC RISK AND MACROECONOMICS TOWARD STOCK RETURN - Emi Pebriyanti (LPPM POLITEKNIK LP3I BANDUNG, 2015)
The objective of this research was to determine the effect of the ratio of bank soundness, systematic risk and macroeconomic to the banking company's stock return period of 2009 to quarter 1 to quarter 3 of 2011 in the Indonesia Stock Exchange. This research uses descriptive method with approach verifikatif event study with a 2 day observation period (h-1 to h-0) or called by the event windows to avoid the bias window at the banking company listings, and actively traded on the Indonesia Stock Exchange. The data used are secondary data derived from financial statements of banking companies first quarter period of 2009 through the third quarter of 2011, BETA, BI Rate and Exchange rate Rupiah against the dollar. While the data analysis method used is multiple regression analysis of panel data using EViews 6.0 program. The test results show that there is simultaneously a significant influence of the ratio of bank soundness (CAR and NPL), systematic risk (BETA) and macroeconomic (BI Rate and Exchange Rate) to the banking company's stock return. The test results also show that the partial positive effect is not significant CAR of the banking company's stock return, the negative effect is not significant NPL for the banking company's stock return, Beta is not significant positive effect on the banking company's stock return, the BI Rate was not significant positive effect on the company's stock return banking and exchange rate are not significantly positive effect on the banking company's stock returns.